Design of integrated radar and communication system based on solvable chaotic signal - Jun-Liang Yao; Mei-Xin He; Yu-Jie Ma; Yun-Fan Yang; Hui-Ping Yin; Hui Hui (Scientific Reports)
Abstract In the integrated radar and communication system (IRCS), the design of signal that can simultaneously satisfy the radar detection and communication transmission is very important and difficult. Recently, some new properties of a class of solvable chaotic system have been studied for wireless applications, such as low bit error rate (BER) wireless communications and low cost target detection. In this paper, a novel IRCS based on the chaotic signal is proposed, and the performance of proposed scheme is analyzed. First, the solvable chaotic system and signal generation method are introduced. Second, the system and frame structures of IRCS using chaos as baseband signal and the corresponding signal processing algorithms are given. Third, the ambiguity function, radar detection errors and communication decoding errors of the proposed scheme are analyzed. Numerous simulations of the proposed IRCS are performed and the simulation results show that the proposed chaotic signal can satisfy the performance requirements of target detection effectively, as well as the high-performance wireless communication. In this context, the proposed IRCS based on chaotic signal is a good choice for the future integrated system.